Coiled-Coil Domain Containing 80 Suppresses Nonylphenol-Induced Colorectal Cancer Cell Proliferation by Inhibiting the Activation of ERK1/2 - Wang, Jing; Zhang, Yuan-wei; Zhang, Nian-jie; Yin, Shuo; Ruan, Du-ji; He, Nian; Chen, Xu; Yang, Xue-feng (Frontiers in Cell and Developmental Biology, 2021)
Recently, the effect of endocrine-disrupting chemicals on the cancer procession has been a concern. Nonylphenol (NP) is a common environmental estrogen that has been shown to enhance the proliferation of colorectal cancer (CRC) cells in our previous studies; however, the underlying mechanism remains unclear. In this study, we confirmed the increased concentration of NP in the serum of patients with colorectal cancer. RNA sequencing was used to explore the differentially expressed genes after NP exposure. We found 16 upregulated genes and 12 downregulated genes in COLO205 cells after NP treatment. Among these differentially expressed genes, we found that CCDC80 was downregulated by NP treatment and was associated with CRC progression. Further experiments revealed that the overexpression of CCDC80 significantly suppressed NP-induced cell proliferation and recovered the reduced cell apoptosis. Meanwhile, the overexpression of CCDC80 significantly inhibited the activation of ERK1/2 induced by NP treatment. ERK1/2 inhibitor (PD98059) treatment also suppressed NP-induced CRC cell growth, but the overexpression of CCDC80 did not enhance the effect of ERK1/2 inhibitor. Taken together, NP treatment significantly inhibited the expression of CCDC80, and the overexpression of CCDC80 suppressed NP-induced CRC cell growth by inhibiting the activation of ERK1/2. These results suggest that NP could induce CRC cell growth by influencing the expression of multiple genes. CCDC80 and ERK1/2 inhibitors may be suitable therapeutic targets in NP-related colorectal cancer progression.